Residential Buildings’ Foundations as a Ground Heat Exchanger and Comparison among Different Types in a Moderate Climate Country - Aresti, Lazaros; Christodoulides, Paul; Panayiotou, Gregoris; Florides, Georgios A. (My University, 2020)
Shallow Geothermal Energy Systems (SGESs) constitute Renewable Energy Systems (RES), which find application in the residential sector through the use of Ground Source Heat Pumps (GSHPs). GSHPs are associated with Ground Heat Exchangers (GHEs), whereby heat is gained/lost through a network of tubes into the ground. GSHPs have failed to flourish in the RES market due to their high initial costs and long payback periods. In this study, the use of Energy Geo-Structure (EGS) systems, namely, the foundation (or energy) piles and the foundation bed of a residential building in Cyprus, was computationally modeled in the COMSOL Multiphysics software. First, the single-houses’ trend in number of units and area in Cyprus was examined and a theoretically typical house with nearly Zero Energy Building (nZEB) characteristics was considered. The heating and cooling loads were estimated in the TRNSYS software environment and used as inputs to investigate the performance of the GSHP/GHE systems. Both systems were shown to exhibit steady performance and high Coefficient of Performance (COP) values, making them an alternative RES solution for residential building integration. Next, the systems were economically evaluated through a comparison with a convectional Air Source Heat Pump (ASHP) system. The economic analysis showed that the cost of the suggested conversions of the foundation elements into GHEs had short payback periods. Consequently, either using the foundation piles or bed as a GHE is a profitable investment and an alternative to conventional RES.
Keywords: Ground heat exchanger; Thermo active structures; Energy geo structures; Foundation bed GHE; Foundation GHE; Energy piles